Economic Valuation of Ecosystem Services and Its Association with Socioeconomic Factors in the Wof-Washa Natural State Forest, North Shewa Zone, Ethiopia - Abere Wondimu Kassie; Admasu Moges; Tilahun Alelign; Gojam Bayeh (Scientifica)
The Wof-Washa Natural State Forest (WWNSF) in Ethiopia harbors remarkable biodiversity but faces threats from local communities, climate change, and a lack of awareness regarding its preservation. Although numerous studies exist, the economic value of the forest’s ecosystem services (FESs) has been largely overlooked. Thus, the purposes of this study were to identify FESs, estimate their total economic value, and assess challenges with possible strategies for sustainable forest management. The research employed Google Earth to estimate forest area and socioeconomic surveys with field visits to gather data from 368 participants for analyzing the FESs, monetary values, and challenges with possible strategies. Analyses included descriptive statistics, total economic valuation (TEV), and an ordinary least squares regression model. The study revealed that the WWNSF provides crucial provisioning services (timber, honey, water, and firewood), regulating services (soil erosion control and climate change mitigation), and supporting services (soil formation and nutrient cycling). The forest’s annual contribution to sampled households averaged $1152.30, with regulating and cultural services valued at $14,112 and $622.00, respectively. The study also revealed that male-headed households, larger families, and those having limited farmland and off-farm income depended more heavily on the forest. Therefore, farmland scarcity, settlements, and tree harvesting for firewood, timber, and agricultural tools, as well as the lack of employment opportunities, were the main challenges encountered in the study area. This suggests that despite degradation and reduction in size due to human pressures, the WWNSF remains a significant source of socioeconomic and ecological benefits, supporting local livelihoods and biodiversity. To ensure the forest’s restoration, prioritizing community participation, promoting family planning, providing alternative income opportunities especially for youth, and balancing resource use with conservation efforts are possible strategies that should be taken into account.